Review Article Breaking the Silence: A Comprehensive Look at Substance Use Among Medical Students.: Substance use disorder in medical students and analysis of its associated factors. (Bombay Hospital Journal, 2024)
Abstract:The study aims to amplify the voices of medical students and gain a better understanding of their perceptions regarding the issue as substance use disorder is a well-known, yet under-represented issue in the medical communityA cross-sectional study of medical students was done using an anonymous online questionnaire to assess demographics, the rationale for continual use, and the students’ perception regarding the issue. The association of various factors leading to substance use was analysed. Statistical associations between the different variables were determined using the Chi- square test, Fisher's Exact Test, and Wilcoxon- Mann-Whitney U Test. A p-value of
Keywords: substance use disorder; medical students; addiction